Kur'an'daki İnfak Kavramının Anlam Yelpazesi - Gül, Ali Riza (Dinî araştırmalar, 2005)
The conception of infâq conveys a wide range of meanings embracing many different conceptions elaborated within the Koran. Infâq is attributed both to Allah -in its metaphorical meaning- and the human beings. The meaning attributed to Allah is understood as granting mankind material subservience. However the meaning attributed to human beings is understood as disposing of the possessed thing and spending them both for themselves and the others, helping the other, based on its lexical meaning. As for the infâq done by the Muslims, together with this lexical meaning is named as zakât (obligatory alms), alms, helping, material contribution to war (provided that it is in the path to Allah), nafaqah, teberru. In addition to all these, the material support provided by the disbelievers in order to destroy Islam and the Muslims, the helps and contributions made by hypocrites (munâfiqûn) to Islam’s army -though they are not good intentions- are assessed in the Koran within the work of infâq